GENERALIZED EQUATIONS FOR METHOD OF PREDICTING OF ROCKS OIL-GAS-WATER-SATURATION IN THE WELLS OPEN-CASTS - Skakalska, L.; Nazarevych, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The aim of the paper is to present the mathematical calculations used in the author’s methodology for predicting the filler type in the rock pores of wells open-casts’ in a generalized form. For creating a method of predicting oil-water-gas-saturation of rock-collectors in the well open-casts we used adequate mathematical model of rock. On the base of this model we developed the general expressions for calculation of elastic waves velocities, porosity and density for rock as the two-phase medium. The model includes the formulae for fluid-saturated and dry rocks. We used the previously derived theoretical and empirical relations for presentation of required characteristic values for the rock solid phase and expressions for calculation of elastic parameters of rocks in the well open-casts. A derivation of the generalized relations for predicting the fluid type in the pores of rock-collectors of wells open-casts and for the layerwise determination of elastic characteristics of rocks are presented. The features of the methodology application are illustrated by concrete examples of calculations based on acoustic logging data. In order to authors’ predicting method the general expressions for the calculation of oil-gas-water-saturation of rocks in well open-casts are derived. The relations of this detection of collectors in rocks of the well open-cast and the differentiation of the rock pores filler types have been obtained for the first time. The mathematical apparatus optimally combines simplicity of the approach with involving the elastic properties of the investigated medium. The derived relations provide a reliable prediction of the rock-collectors’ oil-gas-water-saturation and an effective search for hydrocarbon deposits in the well open-casts.